Increased Cortisol Response and Low Quality of Life in Women Exposed to Intimate Partner Violence With Severe Anxiety and Depression - Cerda-De la O, Beatriz; Cerda-Molina, Ana Lilia; Mayagoitia-Novales, Lilian; de la Cruz-López, Margarita; Biagini-Alarcón, Marcela; Hernández-Zúñiga, Erika Lucia; Borráz-León, Javier I.; Whaley-Sánchez, Jesús Alfredo (Frontiers in Psychiatry, 2022)
Background: Intimate partner violence (IPV) is one of the most prevalent forms of violence against women globally and it is considered a public health problem. Because the experience of IPV is stressful and traumatic for victims, they are at high risk of developing alteration of the Hypothalamus–Pituitary–Adrenal (HPA) axis functioning as well as anxiety and depression symptoms. The aim of this study was to compare the quality of life and changes in cortisol response to an acute stressor between women exposed to IPV and non-exposed women. Differences according to symptoms of anxiety and depression including the risk of suicide thoughts, were also analyzed. Method: Our sample size consisted of 130 women (ages 18 to 68) grouped as follows: 71 women experiencing IPV and 59 women without history of IPV as control group. All participants completed a battery of questionnaires including IPV exposure, anxiety, and depression symptoms (Beck Inventories), as well as quality of life (WHOQOL-BREF). Salivary cortisol levels in response to a cognitive test with verbal, mathematical, and abstract reasoning were measured at four time points. Results: Women exposed to IPV, with severe anxiety and depression symptoms as well as suicide thoughts, exhibited heightened cortisol response after the cognitive test and reported lower quality of life compared to i) women experiencing IPV with moderate symptoms of anxiety and depression, who showed a blunted response, and ii) women without history of IPV with minimal to moderate symptoms, who showed a decreased cortisol profile. Social relationships dimension was in particular the most affected aspect of quality of life. Conclusions: Our findings highlight the role of cortisol responses as a complementary biological marker to be associated with severe psychiatric disturbances in women exposed to IPV.